Analisis Transparansi dan Akuntabilitas Penganggaran Publik: Analysis of Public Budgeting Transparency and Accountability - Nurlina Nurlina (Program Studi Manajemen Keuangan Sektor Publik, Politeknik Wahdah Islamiyah Makassar, 2025)
This study aims to analyze the implementation of transparency and accountability in public budgeting in Indonesia through the implementation of an e-budgeting system. This study uses a literature review method by reviewing various national and international studies published between 2019 and 2025 that are relevant to digital-based public financial governance. The results of the study indicate that e-budgeting contributes significantly to increasing the efficiency of the budgeting process, strengthening information transparency, and creating a digital audit trail that encourages government accountability. This system also allows the public to access budget data in real time, thereby expanding the space for public participation in fiscal policy oversight. However, its implementation still faces various challenges, including limited technological infrastructure, low digital literacy of civil servants, suboptimal data quality, and bureaucratic resistance to change. This study confirms that the success of transparency and accountability is not solely determined by technological innovation but also requires strengthening human resource capacity, consistent political commitment, and a bureaucratic culture that supports openness. These findings are expected to contribute to the development of policy strategies to realize more effective, participatory, and integrity-based public financial governance.